Судьба барабанщика: [повести] / Аркадий Гайдар - Гайдар Аркадий Петрович (Золотая коллекция для юношества, 2011)
Экземпляры: аб (20160208) / Инвентарный номер: 060240 / Цена: 150.00 / Авт.знак: Г 14 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6